2021
DOI: 10.1177/19714009211041530
|View full text |Cite
|
Sign up to set email alerts
|

Dilated MMA sign in cDAVF and other arterial feeders on 3D TOF MRA

Abstract: Background Among the varied causes of pulsatile tinnitus, the condition that can cause severe mortality and morbidity is a cranial dural arteriovenous fistula (cDAVF). This study aimed to assess the diagnostic accuracy of the dilated middle meningeal artery on three-dimensional time-of-flight magnetic resonance angiography in cranial dural arteriovenous fistula and to identify other feeders that can aid in the detection of these lesions. Method Magnetic resonance angiography and digital subtraction angiography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…29 30 Dilatation of the middle meningeal and occipital arteries as well as other branches of the external carotid arteries should be assessed for better detection of a cranial DAVF. 31…”
Section: Radiological Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…29 30 Dilatation of the middle meningeal and occipital arteries as well as other branches of the external carotid arteries should be assessed for better detection of a cranial DAVF. 31…”
Section: Radiological Diagnosismentioning
confidence: 99%
“…29,30 Dilatation of the middle meningeal and occipital arteries as well as other branches of the external carotid arteries should be assessed for better detection of a cranial DAVF. 31 If there is suspicion of DAVF, the patency of the dural sinuses, as well as the cerebral venous drainage patterns, need to be carefully evaluated. [32][33][34] In carotid-cavernous fistulas (CCFs), CT and MRI may demonstrate dilatation of the cavernous sinuses and the superior ophthalmic veins (►Figs.…”
Section: Radiological Diagnosismentioning
confidence: 99%
“…Studies have reported that the sensitivity of TOF-MRA in diagnosing DAVF is 79.49% (95% confidence interval CI: 66.81%–92.16%), with a specificity of 100% (95% CI: 100.00%–100.00%). 33 The main diagnostic key is the identification of the feeding artery (middle meningeal artery). Original TOF-MRA images with high spatial resolution have proven to be useful screening tools for DAVFs.…”
Section: Conventional Mri For Davfsmentioning
confidence: 99%